112 Increasing Rates of Imaging in Failed Back Surgery Syndrome (FBSS) Patients: A 10-Year Perspective. (August 2015) - Petraglia, Frank William; Farber, S. Harrison; Thomas, Steven M.; Wang, Frances; Churchill, Levis Eric; Lad, Shivanand P.
Abstract : INTRODUCTION: Failed Back Surgery Syndrome (FBSS) is notoriously refractory to treatment resulting in high health care utilization and high health care costs. Given the recent emphasis of cost-conscious care in the United States, we examined the trends in imaging use in FBSS over the past decade. Furthermore, the role of different types of imaging modalities MRI vs non-MRI is of interest when considering potential therapeutic interventions, including spinal cord stimulation (SCS), a common therapy for treating neuropathic pain in the FBSS population. METHODS: We conducted a retrospective analysis using the Truven MarketScan database to analyze the rates of imaging use in FBSS patients between the years 2000 and 2009. Total imaging episodes were computed for magnetic resonance imaging (MRI), computed tomography (CT) scan, x-ray, ultrasound, and nuclear imaging. In order to compare imaging usage between years which contain different numbers of patients, imaging rates were calculated using number of imaging episodes per 1000 patient months for each year. RESULTS: The yearly imaging rates for each modality are outlined in Table 1. The overall imaging rate for FBSS patients increased by 39% over the past decade. Specifically, the MRI imaging rate increased 35% from 29.5 to 39.9, and the non-MRI imaging rate increased 39% from 305.1 to 424.1. All imaging modalities showed increased usage between 2000 and 2009 with the exception of x-ray. The x-ray rate remained relatively constant at 234.8 in 2000 and 238.6 in 2009. CONCLUSION: We found a trend for increased imaging use between 2000 and 2009 in FBSS patients, a population with already immense health care utilization and health care costs. Rates of both MRI and non-MRI imaging increased by 35% to 40% in a period of 10 years. The role of frequency and type of imaging modality utilized in evaluating FBSS patients will have a significant impact on overall health care expenses and therapeutic options, including SCS, going forward.